Using Surface Immunogenic Protein as a Carrier Protein to Elicit Protective Antibody to Multiple Serotypes for Candidate Group B Streptococcal Glycan Conjugate Vaccines - Huiqi Duan; Wenhua Huang; Qingyu Lv; Peng Liu; Qian Li; Decong Kong; Xuyang Sun; Xinran Zhang; Yongqiang Jiang; Shaolong Chen (Vaccines, 2024)
Group B Streptococcus (GBS) is a life-threatening opportunistic pathogen, particularly in pregnant women, infants, and the elderly. Currently, maternal vaccination is considered the most viable long-term option for preventing GBS mother-to-infant infection, and two polysaccharide conjugate vaccines utilizing CRM197 as a carrier protein have undergone clinical phase II trials. Surface immunogenic protein (Sip), present in all identified serotypes of GBS strains so far, is a protective surface protein of GBS. In this study, the type Ia capsular polysaccharide (CPS) of GBS was utilized as a model to develop candidate antigens for a polysaccharide conjugate vaccine by coupling it with the Sip of GBS and the traditional carrier protein CRM197. Serum analysis from immunized New Zealand rabbits and CD1 mice revealed that there was no significant difference in antibody titers between the Ia-Sip group and Ia-CRM197 group; however, both were significantly higher than those observed in the Ia polysaccharide group. Opsonophagocytosis and passive immune protection results using rabbit serum indicated no significant difference between the Ia-Sip and Ia-CRM197 groups, both outperforming the Ia polysaccharide group. Furthermore, serum from the Ia-Sip group had a cross-protective effect on multiple types of GBS strains. The challenge test results in CD1 mice demonstrated that the Ia-Sip group provided complete protection against lethal doses of bacteria and also showed cross-protection against type III strain. Our study demonstrates for the first time that Ia-Sip is immunogenic and provides serotype-independent protection in glycan conjugate vaccines, which also indicates Sip may serve as an excellent carrier protein for GBS glycan conjugate vaccines and provide cross-protection against multiple GBS strains.